2018
DOI: 10.1007/s11701-018-0847-9
|View full text |Cite
|
Sign up to set email alerts
|

Standard vs delayed ligature of the dorsal vascular complex during robot-assisted radical prostatectomy: results from a randomized controlled trial

Abstract: Standard and delayed approaches to DVC are safe and lead to similar functional outcomes. A delayed approach exposes to a higher risk of PSM in organ-confined disease but with a lower risk of apical involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…As a consequence, the most accepted alternative approach consists of the direct resection of the DVC at the end of prostatectomy, going for suture afterwards. This approach is generally dominated by delayed ligature of the DVC or selective ligature of the DVC (the D-DVC technique) [ 3 ]. Li et al [ 13 ] evaluated current views on comparing the D-DVC with the S-DVC for safety, urinary control and oncological outcomes during LRP and concluded that the D-DVC could decrease the positive apical margin rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the most accepted alternative approach consists of the direct resection of the DVC at the end of prostatectomy, going for suture afterwards. This approach is generally dominated by delayed ligature of the DVC or selective ligature of the DVC (the D-DVC technique) [ 3 ]. Li et al [ 13 ] evaluated current views on comparing the D-DVC with the S-DVC for safety, urinary control and oncological outcomes during LRP and concluded that the D-DVC could decrease the positive apical margin rate.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed ligature of the DVC (D-DVC) firstly transects the DVC, followed by selective suture ligation of the DVC. D-DVC technique is also widely used in the laparoscopic surgery under pneumoperitoneum [ 3 ]. However both techniques are difficult steps for novice surgeons because the S-DVC needs precise needle passage in suturing the DVC and the depth of the stitch for ligation is not always clear [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…See Supplementary Table 2 and results section for further details Fig. 5 Blood transfusion is associated with the risk of prolonged length of hospital stay in 980 patients who underwent robot-assisted radical prostatectomy as a primary treatment for prostate cancer (corrected odds ratio, OR 1.633 with 95% CI ranging from 1.411 to 1.889) tumor-resulting in a less accurate dissection of the tumor with a higher risk of positive surgical margins and an increased risk of cancer recurrence and progression due to immune system suppression [24,27]. The results of our study suggest that patients should be counseled on the risk of perioperative blood transfusion and the implications related to this unfavorable event.…”
Section: Discussionmentioning
confidence: 99%
“…Severe intraoperative bleeding with perioperative blood transfusion, might carry potential oncological drawbacks. The hemorrhage may obscure the view of the tumor-resulting in a less accurate dissection of the tumor with a higher risk of positive surgical margins and an increased risk of cancer recurrence and progression due to immune system suppression [ 24 , 27 ]. The results of our study suggest that patients should be counseled on the risk of perioperative blood transfusion and the implications related to this unfavorable event.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation